Headcover and male-pattern hair loss: A cross-sectional study - Mohammed I AlJasser; Mohammed Alshaya; Khaled Alabduljabbar; Sara I Altraif; Sultan Aleshaiwi; Emad Masuadi (Wolters Kluwer Medknow Publications, 2019)
Background: Androgenetic alopecia (AGA) is the most common form of alopecia. The interaction of genetics and environmental factors likely plays a role in its pathogenesis. Several environmental factors have been studied in relation to the severity of AGA; however, the effect of headcover has not been properly assessed. Objectives: The objective of this study is to assess the severity of male-pattern hair loss (MPHL) in relation to headcover. Methods: Adult males with varying degrees of MPHL were recruited during the period from May 2016 to August 2017. Data included demographics and type of headcover. The total duration of headcover was calculated for every participant in years. Assessment of MPHL was performed using the Norwood-Hamilton classification. Results: A total of 865 participants with MPHL were enrolled. No statistically significant difference in the severity of MPHL was found between participants who covered their head frequently as compared to those who did not (P = 0.952). Multivariate logistic regression analysis showed that age was the only factor associated with increased severity of MPHL. Conclusions: Males who cover their head do not appear to have increased overall severity of MPHL.